Neuroprotective effects of resistance physical exercise on the APP/PS1 mouse model of Alzheimer’s disease - Campos, Henrique Correia; Ribeiro, Deidiane Elisa; Hashiguchi, Debora; Glaser, Talita; Milanis, Milena da Silva; Gimenes, Christiane; Suchecki, Deborah; Arida, Ricardo Mario; Ulrich, Henning; Monteiro Longo, Beatriz (Frontiers in Neuroscience, 2023)
Introduction Physical exercise has beneficial effects by providing neuroprotective and anti-inflammatory responses to AD. Most studies, however, have been conducted with aerobic exercises, and few have investigated the effects of other modalities that also show positive effects on AD, such as resistance exercise (RE). In addition to its benefits in developing muscle strength, balance and muscular endurance favoring improvements in the quality of life of the elderly, RE reduces amyloid load and local inflammation, promotes memory and cognitive improvements, and protects the cortex and hippocampus from the degeneration that occurs in AD. Similar to AD patients, double-transgenic APPswe/PS1dE9 (APP/PS1) mice exhibit Αβ plaques in the cortex and hippocampus, hyperlocomotion, memory deficits, and exacerbated inflammatory response. Therefore, the aim of this study was to investigate the effects of 4 weeks of RE intermittent training on the prevention and recovery from these AD-related neuropathological conditions in APP/PS1 mice. Methods For this purpose, 6-7-month-old male APP/PS1 transgenic mice and their littermates, negative for the mutations (CTRL), were distributed into three groups: CTRL, APP/PS1, APP/PS1+RE. RE training lasted four weeks and, at the end of the program, the animals were tested in the open field test for locomotor activity and in the object recognition test for recognition memory evaluation. The brains were collected for immunohistochemical analysis of Aβ plaques and microglia, and blood was collected for plasma corticosterone by ELISA assay. Results APP/PS1 transgenic sedentary mice showed increased hippocampal Aβ plaques and higher plasma corticosterone levels, as well as hyperlocomotion and reduced central crossings in the open field test, compared to APP/PS1 exercised and control animals. The intermittent program of RE was able to recover the behavioral, corticosterone and Aβ alterations to the CTRL levels. In addition, the RE protocol increased the number of microglial cells in the hippocampus of APP/PS1 mice. Despite these alterations, no memory impairment was observed in APP/PS1 mice in the novel object recognition test. Discussion Altogether, the present results suggest that RE plays a role in alleviating AD symptoms, and highlight the beneficial effects of RE training as a complementary treatment for AD.